THE COMPREHENSIVE SYSTEMATIC REVIEW OF HYPERTENSIVE DISORDERS IN PREGNANCY AND LONG TERM RISK OF MATERNAL STROKE - Supriyadi, Agung; Andimapali, Zulfikar; Fitria, Adina; Whisnu Dewanegara, Rahadiyan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Hypertensive disorders of pregnancy (HDP) are associated with a long-term risk for cardiovascular disease among parous patients later in life. However, relatively little is known about whether HDP are associated with an increased risk for ischaemic stroke (IS) or haemorrhagic stroke (HS) in later life. The aim: This study aims to show about the comprehensive of hypertensive disorders in pregnancy and long term risk of maternal stroke. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 67 articles, whereas the results of our search on SagePub brought up 170 articles. The results of the search conducted for the last year of 2014 yielded a total 35 articles for PubMed and 58 articles for SagePub. The result from title screening, a total 15 articles for PubMed and 29 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Exposure to Hypertensive disorders of pregnancy (HDP), including PE and GH, seems to be associated with an increased risk for AS and IS among parous patients in later life. Preventive interventions may be warranted for patients who experience HDP to reduce their long-term risk for stroke.